2021
DOI: 10.1021/acs.jmedchem.0c01804
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Analogues of the Chemerin C-Terminus Mimic a Loop Conformation Essential for Activating the Chemokine-like Receptor 1

Abstract: The chemokine-like receptor 1 (CMKLR1) is a promising target for treating autoinflammatory diseases, cancer, and reproductive disorders. However, the interaction between CMKLR1 and its protein–ligand chemerin remains uncharacterized, and no drugs targeting this interaction have passed clinical trials. Here, we identify the binding mode of chemerin-9, the C-terminus of chemerin, at the receptor by combining complementary mutagenesis with structure-based modeling. Incorporating our experimental data, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…We previously showed that cyclic chemerin-9 derivates activate CMKLR1 with high potency, and the same holds true for GPR1 (Fig. 6) [27]. This highlights that the binding mode of the chemerin C-terminus is highly related at both receptors.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…We previously showed that cyclic chemerin-9 derivates activate CMKLR1 with high potency, and the same holds true for GPR1 (Fig. 6) [27]. This highlights that the binding mode of the chemerin C-terminus is highly related at both receptors.…”
Section: Discussionsupporting
confidence: 65%
“…First, we determined the minimal portion of the chemerin protein needed for full arrestin recruitment, our functional readout, in order to identify the portion of chemerin that engages the receptor. In parallel, we constructed a comparative model of GPR1 to identify candidate residues in the extracellular loops and the upper portions of the transmembrane (TM) helices that can form the putative binding site for chemerin; this was done bearing in mind the previously identi ed binding pocket of chemerin at the CMKLR1 [27]. Consequently, we determined an interaction point by complementary mutagenesis, and probed the internal conformation of the minimal activation sequence employing cyclized peptides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations